Catastrophic health care, poverty, and impoverishment in the Philippines - Ico, Ronaldo D. ([Quezon City] School of Economics, University of the Philippines, 2008)
The paper attempts to describe catastrophic health spending and its impact on poverty in the Philippine setting. It focuses on the role of out-of-pocket payments for health care as a springboard for measuring the magnitude and analyzing the extent of damage of catastrophic health expenditures. It also explores the scope and trends of health spending in terms of different socioeconomic indicators. More importantly, it delves into trends over time and among different income groups.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (page 126)
Keywords: Medical care -- Philippines; Medical care -- Utilization -- Philippines; Medical care, Cost of -- Philippines; Health services administration -- Philippines; Public health administration -- Philippines